Phytochemical Analysis and Study of Antioxidant and Antimicrobial Activities of Two Parts of Cupressus arizonica Essential Oils - Sara Cherrad; Imane Jaouadi; Abdelhakim Bouyahya; Loubna Koursaoui; El Mahjoub Aouane; Badr Satrani; Mujeeb A. Sultan; Amal Alotaibi; Riaz Ullah; Mohamed Ghanmi; Abdelaziz Chaouch (Journal of Food Quality)
The present work aimed to determine the difference in the chemical composition of essential oils isolated from two parts of Cupressus arizonica and to evaluate their in vitro antimicrobial and antioxidant effects. The yields of the essential oil obtained by hydrodistillation from the leaves and cones were 0.85% and 1.29%, respectively. The chemical analysis of the constituents of the two essential oils of Cupressus arizonica was carried out by using the GC and GC/MS techniques. The results of this analysis show that the leaves are dominated by cis-muurola-4 (14), 5-diene (21.27%), umbellulone (19.88%), α-pinene (9.39%), and α-muurolene (7.87%7); on the other hand, the cones are rich in α-pinene (51.07%) accompanied by other variable content constituents, myrcene (17.92%), limonene (9.66%), β-pinene (4.92%), meta-cymenene (2.6%), and α-terpineol (2.38%). The antimicrobial activity against four bacterial strains, four wood decay fungi, and three mould strains were determined using the agar-agar dispersion method. The studied essential oils exhibited moderate antimicrobial properties, which demonstrates the sensibility of all strains tested with the exception of wood rot fungi to which they do not have activity against all concentrations tested. The dosage of antioxidant activity was evaluated using DPPH scavenging and ferric ion reducing power (FRAP). The results indicate that the essential oils from cones of Cupressus arizonica possess a strong antioxidant activity (lower IC50) IC50 = 0.098 ± 0.008/EC50 = 0.646 ± 0.02) in comparison with those from the leaves (IC50 = 5.297 ± 0.09/EC50 = 2.335 ± 0.36). The results suggest that both essential oils could be used as a source of treatment for bacterial infections and also as natural antioxidant substances.